The Impact of MicroRNA-223-3p on IL-17 Receptor D Expression in Synovial Cells - Moriya, Nozomu (PLoS One, 2017)
OBJECTIVE: Rheumatoid arthritis (RA) is an autoimmune inflammatory disease affecting joints. Elevated plasma levels of microRNA-223-3p (miR-223-3p) in patients with RA are implicated in the pathogenesis of the disease. This study aimed to analyze the functional role of miR-223-3p in the pathogenesis of RA by overexpressing miR-223-3p in synovial cell lines. METHODS: Arthritis was induced in the RA model of SKG mice by injection of ß-glucan. The histopathologic features of joints were examined using hematoxylin and eosin and immunohistochemical staining. Plasma levels of miRNA were determined by panel real-time PCR analysis. Target genes of the differentially expressed miRNAs in SKG mice were analyzed using miRNA target prediction algorithms. The dual-luciferase reporter system was used to evaluate the relationship between miR-223-3p and IL-17 receptor D (IL-17RD). The activity of miR-223-3p was analyzed by transfection of plasmid vectors overexpressing miR-223-3p into IL-17RD-expressing NIH3T3 and MH7A cell lines. Il6 and Il17rd mRNA expression was analyzed by quantitative real-time PCR. IL-17RD protein expression was analyzed by western blot analysis. RESULTS: We identified 17 upregulated miRNAs (fold change > 2.0) in plasma of SKG mice injected with ß-glucan relative to untreated SKG mice. Il17rd was identified as the candidate target gene of miR-223-3p using five miRNA target prediction algorithms. The transfection of plasmid vectors overexpressing miR-223-3p into NIH3T3 and MH7A cells resulted in the downregulation of Il17rd expression and upregulation of Il6 expression. Expression of miR-223-3p and Il6 mRNA in MH7A cells was upregulated; however, that of Il17rd mRNA was downregulated following TNF-α stimulation. IL-17RD expression in synovial tissues from SKG mice and RA patients was inversely correlated with the severity of arthritis. CONCLUSION: This study is the first to demonstrate that miR-223-3p downregulates IL-17RD in both mouse and human cells; miR-223-3p may contribute to the pathogenesis of RA by downregulating the expression of IL-17RD and upregulating that of IL-6 in synovial cells.